Reclaiming indigeneity and democracy in India`s Jharkhand - Basu, Ipshita (United Kingdom Oxford university press, 2024)
In 'Reclaiming Indigeneity and Democracy in India's Jharkhand', Ipshita Basu contributes to scholarship on critical social justice and indigeneity by highlighting 'relations of justification' as a central feature of group-based claims-making for social groups identifying with indigeneity in diverse ways. Specifically, the book focuses on reclaiming political recognition for Adivasis within the contemporary dynamics of majoritarian populism and the market economy
Keywords: Democracy India Jharkhand; Politics and Government; India Jharkhand